2021
DOI: 10.48550/arxiv.2101.02566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Approximation of wave packets on the real line

Abstract: In this paper we compare three different orthogonal systems in L2(R) which can be used in the construction of a spectral method for solving the semi-classically scaled time dependent Schrödinger equation on the real line, specifically, stretched Fourier functions, Hermite functions and Malmquist-Takenaka functions. All three have banded skew-Hermitian differentiation matrices, which greatly simplifies their implementation in a spectral method, while ensuring that the numerical solution is unitary -this is esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Remark 2.3. Recently, Iserles, Luong and Webb in [19] compared the approximation power of the Malmquist-Takenaka, Hermite and stretched Fourier functions for Gaussian wave packet functions of the form f (x) = exp(−β(x − x 0 ) 2 ) cos(ωx), where β > 0 and x 0 , ω ∈ R. After some lengthy algebra, they derived the decay rates of the coefficients with respect to these three orthogonal systems, respectively, and concluded that the MTFs are superior to the other two functions. Note that all those three functions have banded skew-Hermitian differentiation matrices.…”
Section: Malmquist-takenaka Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark 2.3. Recently, Iserles, Luong and Webb in [19] compared the approximation power of the Malmquist-Takenaka, Hermite and stretched Fourier functions for Gaussian wave packet functions of the form f (x) = exp(−β(x − x 0 ) 2 ) cos(ωx), where β > 0 and x 0 , ω ∈ R. After some lengthy algebra, they derived the decay rates of the coefficients with respect to these three orthogonal systems, respectively, and concluded that the MTFs are superior to the other two functions. Note that all those three functions have banded skew-Hermitian differentiation matrices.…”
Section: Malmquist-takenaka Functionsmentioning
confidence: 99%
“…where δ n,m is the Kronecker delta. Theoretical aspects of MTFs as well as their applications in designing algorithms for Fourier and Hilbert transforms have been investigated during the past few decades (see, e.g., [8,15,18,19,35,36]). We list below some of theoretical properties of MTFs that will be used for the construction of spectral method.…”
Section: Malmquist-takenaka Functionsmentioning
confidence: 99%